Understanding of occupational health and safety risks and participatory practices in small businesses : qualitative case studies of three small cafe and restaurant businesses : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Occupational Health and Safety (Human Resources Management) at Massey University, Manawatu, New Zealand - Pandey, Bikram Raj (Massey University, 2013)
Small businesses are generally characterised as having highly hazardous working environments and significant exposure to occupational health and safety (OHS) risks. Regulation, irrespective of the size and nature, requires all businesses to take reasonable measures to minimise hazards and hazardous exposures. Limited resource availability and limited market share, in particular, differentiate SBs from large ones in relation to OHS practices such as the identification of OHS hazards, reduction of hazardous exposures and minimisation of risks. Further the owner-managed nature of the operation, manifesting informal human resource management practices and employment relations, makes them unique and different from large businesses in relation to OHS practices. Nevertheless, the informal social relation and the local work environment context where the employer works alongside employees facing the same hazards is considered to provide a unique opportunity to owner/managers and employees to establish a similar/common understanding of OHS risks, and thus a better opportunity for hazards and risk control in SBs. The understanding of OHS hazards and risks in the local work environment context is called the local theory (of work environment). The local theory is deemed indispensable for participatory practice (participation by both owner/manager and employees) in the identification and control of OHS hazards and risks. However, an understanding of OHS risks and participation in the identification and control of OHS hazards and risks in the local work environment in SBs has been little studied. Importantly, there has not been any precedence in the use of the local theory of work environment (LTWE) to explore an understanding of OHS risks and participation in the identification and (local understanding) control of OHS hazards and risks in SBs. Therefore, the objective of this study was to explore the owner/managers’ and employees’ understanding of OHS risks and their participation in the identification and control of hazards and risks using the four elements of the LTWE: experience, causal relations, legitimisation and action. Qualitative case studies of three SBs, employing between six to 19 employees, was undertaken to examine local understanding of OHS risks and participation in identification and control of OHS hazards and risks. This involved ethnographic field observations and semi-structured interviews with the employer and employees in three independently owned restaurants and cafes from the Manawatu region of the Central i North Island, New Zealand. Data obtained from interview responses and field observations were analysed thematically. The four elements of the LTWE as the units of analysis, in combination with the techniques of network diagram, were used to examine understanding of OHS risks in the local work environment. The technique of typology development was used to understand participation in the identification and control of OHS hazards and risks. The study showed that the employers’ and employees’ understanding of OHS risks was experiential such that primarily the directly experienced obvious, physical and immediate effect hazards, events and consequences were understood as OHS risks. Experience of hazards that can be associated or not with immediate effects was related to the construction of similar or different understandings of OHS risks between the owner/manager and employees. The element of legitimisation – the ability to bring up issues and the accepted reasons allowing them to bring up hazards and risks for discussion and broader attention in the local work environment – was pivotal to the development of similar or different understandings of OHS risks in the local work environment. The understanding of OHS risks by the owner/manager and employees depicted the local theory, which consequently determined participation by the owner/manager and employees in the identification and control of hazards and risks and the approaches considered appropriate for hazards identification and control. Understanding of OHS risks, the construction of a local theory and participation in the identification and control of OHS risks were different from one case to the other as were their characteristic contexts. Open participation, lead-through participation and closed participation were the three different typologies of participation that were observed predominantly in each of the three business cases, respectively. An important finding of the study was that the different typologies of participation influenced legitimisation of OHS hazards and risks differently, which was observed to determine the way hazards and risks were dealt with. Open participation was observed to legitimise most OHS issues unselectively and take the approach of elimination to control hazards and risks, as opposed to a closed participation, which allowed selective legitimisation of OHS issues tending largely to be an approach of minimisation to control hazards and risks. The findings suggest that the management of hazards in SBs is informal and reactive in nature and that by expanding and extending the sphere of legitimisation, through a more structured approach to hazard identification and recognition, it is possible to establish a more predictive (proactive) hazard management strategy. This, in turn, could lead to a more open participatory work environment, where more appropriate (and potentially more effective approaches) to the control of hazards and risk would be employed.
Keywords: Occupational Health and Safety (OHS); Small businesses; Small business case studies; Local theory of work environment (LTWE); Industrial safety